The embattled self : French soldiers' testimony of the Great War - Smith, Leonard V., 1957- (Cornell University Press, 2007)
How did the soldiers in the trenches of the Great War understand and explain battlefield experience, and themselves through that experience? Situated at the intersection of military history and cultural history, The embattled self draws on the testimony of French combatants to explore how combatants came to terms with the war. In order to do so, they used a variety of narrative tools at hand-- rites of passage, mastery, a character of the soldier as a consenting citizen of the Republic. None of the resulting versions of the story provided a completely consistent narrative, and all raised more questions about the "truth" of experience than they answered. In thematic chapters, Smith explains why the novel structured by a specific notion of trauma prevailed by the 1930s and undermines the conventional understanding of the war as tragedy and its soldiers as victims, a view that has dominated both scholarly and popular opinion since the interwar period